ANALISIS KEMAMPUAN DAN KEMAUAN MEMBAYAR PELANGGAN PADA WISATA PELANGI DI KOTA TIMIKA - Yahya Nusa; Hasniaty (CV. ADIBA AISHA AMIRA, 2023)
This study aims to find out how the ability to pay customers on rainbow tours from the ticket prices and facilities provided by the tour, and find out how the willingness to pay customers on rainbow tours from the tickets and facilities provided by the tour. The method used by researchers is descriptive method. Data collection techniques in this study were observation, literature study and distributing 100 questionnaires to rainbow tourism customers. The analytical tools used in this study are Ability to Pay and Willingnes To Pay. The results of the analysis show that the customer's Ability to Pay is greater than Willingnes To Pay (willingness to pay) because customers feel dissatisfied with the facilities provided by Pelangi Tours in Timika City